Effect on Overall Health Status With Weightbearing at 2 Weeks vs 6 Weeks After Open Reduction and Internal Fixation of Ankle Fractures. (June 2020) - Schubert, Jonathon; Lambers, Kaj T. A.; Kimber, Cheryl; Denk, Katharina; Cho, Matthew; Doornberg, Job N.; Jaarsma, Ruurd L.
Background: Ongoing controversy exists on postoperative weightbearing status after open reduction and internal fixation of an ankle fracture. This prospective randomized controlled trial aimed to compare patient-based and physician-based outcomes after early weightbearing at 2 vs 6 weeks postoperatively. Methods: Fifty patients with unstable rotational-type ankle fractures were treated operatively with subsequent immobilization in a below-the-knee cast for 2 weeks and were then randomly allocated to 2 groups. The first group had early weightbearing at 2 weeks postoperation and the second group at 6 weeks postoperation. Follow-up included subjective and objective evaluations performed at 2, 6, 12, and 26 weeks postoperatively. The primary outcome was the patient-based general health status as measured with the EuroQol-5D (EQ-5D) scoring system. Secondary outcome was the Olerud and Molander ankle score. Power analysis revealed a study group of 50 patients was needed to show a clinically relevant effect size of 10 points in both EQ-5D visual analog scale (VAS) score and Olerud and Molander score. Results: Patients in the early weightbearing group had higher mean EQ-5D VAS scores at a 6-week follow-up ( P = .014) of 77 ± 14 compared to 66 ± 15 for late mobilization. No difference was found at other follow-up points or between groups for physician-based outcome measures. At 26 weeks postoperatively, mean Olerud and Molander ankle scores were similar at 84 ± 16 and 81 ± 17 for mobilization at 2 and 6 weeks postoperation, respectively. Conclusion: Early weightbearing after operative fixation of rotational-type ankle fractures had a clinically relevant and statistically significant benefit in patient-based general health status, as quantified with EQ-5D VAS scores, at 6 weeks postoperation. These results contribute to our understanding of early weightbearing and may encourage consideration of weightbearing at 2 weeks postoperatively in standard protocols. Level of Evidence: Therapeutic Level I, prospective randomized controlled trial.